Analysis of factors influencing strategies and expectations of Czech new start-ups - Šála, Miroslav; Lukeš, Martin, 1976-; Jaklová, Martina L.; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
This thesis goal is to analyze the factors that are influencing the strategies and growth expectations of the Czech start-ups. The analysis is based on the data sample from the Czech GEM 2011 and unique study of the Czech start-ups performed in 2011 as well. Various statistical methods are used to determine which microeconomic factors affect (1) the strategy choice and (2) growth expectations. As for the factors influencing expected growth, the research is concluded by the creation of the regression equations explaining the expected growth in the revenues as well as expected growth in employees. The factors influencing strategy choice are: managers-owners experience, the environment, self-efficacy, gender, and innovativeness. The factors influencing expected growth in revenues are: innovativeness, self-efficacy, competitive strategy, managers-owners experience, social capital, export intention, and business planning. The factors influencing the expected growth in employment are: legal structure of company, export intention, self-efficacy, innovativeness, competitive strategy, business planning. Following variables create the regression equation explaining expected growth in revenues: financial planning, export intention, education, IPR use, and age of entrepreneur. The variables explaining expected growth in employees are: (1) export intention, product newness, and legal structure of the company, (2) product newness, differentiation inclination, and financial projections. Alongside, the Porter's generic strategies framework was proved to fit the data sample while it was showed that a portion of Czech entrepreneurs are "stuck in the middle". By these findings, this thesis provides unique empirical verification of the growth and strategy theory on the sample of the Czech entrepreneurs.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses